Cost‐effectiveness analysis of dabigatran, rivaroxaban and warfarin in the prevention of stroke in patients with atrial fibrillation in China - Wei, Hongtao (BMC Health Serv Res, 2021)
BACKGROUND AND OBJECTIVE: To evaluate the cost-effectiveness of new anticoagulants and warfarin in the prevention of stroke in Chinese patients with atrial fibrillation (AF). METHODS: The Markov model was constructed to compare patients’ quality-adjusted life-years (QALYs) using drug cost, the cost of the examination after taking a drug, and the incremental cost of other treatments. Both dabigatran (110 and 150 mg, twice a day) and rivaroxaban (20 mg, once a day) were compared with warfarin (3–6 mg, once a day). Willingness to pay, three times the 2018 China GDP per capita (9481.88 $), was the cost-effect threshold in our study. RESULTS: The total cost were was 5317.31$, 29673.33$, 23615.49$, and 34324.91$ for warfarin, rivaroxaban, dabigatran 110 mg bid, and dabigatran 150 mg bid, respectively. The QALYs for each of the four interventions were 11.07 years, 15.46 years, 12.4 years, and 15 years, respectively. The cost-effectiveness analysis of the three new oral anticoagulants and warfarin showed that the incremental cost-effectiveness ratio (ICER) was 5548.07$/QALY when rivaroxaban was compared with warfarin. Rivaroxaban was the most cost-effective choice and warfarin was the least. CONCLUSIONS: In Chinese patients with AF, although warfarin is cheaper, rivaroxaban has a better cost-effectiveness advantage from an economic point of view.